A study of microstructure and mechanical properties of copper filled polypropylene and copper filled epoxy - Nor Riza Kamalul Baharim
In this final year project, metal filled polymer composite had been produced by using powder metallurgy concept and cold pressing method. The processing method had influenced the properties of composite system and to establish the quantitative relationship between the mixing ratios and its final properties.